Multicomponent reactions for the synthesis of heterocycles - Jiang, Bo; Rajale, Trideep; Wever, Walter; Tu, Shu-Jiang; Li, Guigen (Chemistry, an Asian journal, 2010)
Multicomponent domino reactions (MDRs) serve as a rapid and efficient tool for the synthesis of versatile heterocycles, particularly those containing structural diversity and complexity, by a one-pot operation. These reactions can dramatically reduce the generation of chemical wastes, costs of starting materials, and the use of energy and manpower. Moreover, the reaction period can be substantially shortened. This Review covers recent advances on multicomponent domino reactions for the construction of five-, six-, and seven-membered heterocyclic skeletons and their multicyclic derivatives.